1999
DOI: 10.1088/0022-3727/32/10/310
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted synthesis of N2O5from NO2in air at atmospheric pressure using a dielectric pellet bed reactor

Abstract: It has been demonstrated that a dielectric packed pellet-bed plasma reactor operating on a mixture of NO 2 in air at atmospheric pressure can be used as an efficient method for the synthesis of dinitrogen pentoxide, N 2 O 5 . The reactor is packed with glass beads and operates at high frequency (10-13 kHz) and high voltage (V pk−pk < 30 kV). Typically, the energy density is 38 J l −1 and 45 ppm of NO 2 is converted into 53 ppm of N 2 O 5 . The synthesis of N 2 O 5 is found to be plasma-assisted in the sense th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 78%
“…It should be noted that total NO x reduction cannot be concluded from considering the effect of plasma on NO, NO 2 and N 2 O only. Other nitrogen oxides such as NO 3 and N 2 O 5 can be formed during the process, and they should be considered in future applications (Fitzsimmons et al 1999). …”
Section: Effect Of Non-thermal Plasma On No X Concentrationmentioning
confidence: 99%
“…Igniting a discharge in this gas composition leads to the formation of ozone (O 3 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), carbon dioxide (CO 2 ) and carbonyl fluoride (COF 2 ). Furthermore, a band at 1 720 cm −1 was detected and identified as dinitrogen pentoxide (N 2 O 5 ) 20…”
Section: Resultsmentioning
confidence: 99%
“…[2] The N 2 gas reacts with O 3 in the ozone generator to create N 2 O 5 and N 2 O, which are known as stable products in N 2 /O 2 plasma reactions. [6] (Fig. 3).…”
Section: Ftir Spectra Of Ozone Gas From Ozone Generatormentioning
confidence: 97%